"We need to find a revenue model": Data journalists' perceptions on the challenges of practicing data journalism in India - Kashyap,Geeta (2020)
Data journalism is emerging as a new subspecialty in Indian journalism. Indian data journalism practice is in nascent stage and newsrooms have lately started recognizing it as a new practice. There were specific issues and challenges faced by journalists in western news rooms as they adopted the practice. To generate a comparative perspective, the study carried out semi-structured interviews with Indian data journalists about their perceptions on the challenges of practicing data journalism. The results show that there are external and internal bottlenecks in practicing data journalism in India. While irregular data releases, use of unfriendly formats by governmental authorities is a major concern; reluctance of media organizations to invest in data teams is identified as an internal challenge. Indian data journalists are skeptical about the audience's participatory potential, which has restricted them from relying on practices like crowd-sourcing.